Structural deformation characteristics and its influence on shale gas preservation of the Wufeng−Longmaxi Formation in the Wuxi area, Chongqing, China - Li, Wei; Luo, Tongtong; Yu, Chuan; Tian, Xuesong; Sun, Chaoya; Wang, Wei; Wang, Shengxiu; Zhong, Zheng; Zhang, Ye; Liu, Jun (Frontiers in Earth Science, 2023)
The Upper Ordovician Wufeng to Lower Silurian Longmaxi Formation has a good material basis for marine shale gas development , and the structural preservation conditions are the key factors to control the rich and integrated shale gas reservoirs in the Wuxi area of Chongqing City, China. Based on the seismic structural interpretation data, combined with the regional structural background and drilling effect, the structural deformation characteristics and shale gas structural preservation conditions are comprehensively analyzed in the study area. The Wuxi area is located at the structural junction of Sichuan Basin and southern Dabashan along with strong structural deformation. Seven rows of NW to near EW structural belts are mainly developed. The fold styles and fault development degrees of different structural belts are different, and the difference among the structural preservation conditions of shale gas are also very obvious.The studied results reveal that the shale gas structure preservation conditions of Wufeng-Longmaxi Formation in the Wuxi area are overall poor, only local better. The structure preservation conditions for shale gas enrichment and accumulation are divided into four grades, such as the good Class I area, the general Class II area, the poor Class III area and the very poor Class IV. Among them, the Heiloumen structural zone and Huangcaoping buried structural zone nearby the Sichuan Basin have good preservation conditions and are classified into the good Class I preservation area.The macroscopic preservation type of shale gas in the Wufeng-Longmaxi Formation of the Wuxi area belongs to the complex structural preservation of basin margin. Three structural preservation modes of shale gas in the study area have also been confirmed, including lost destruction type, lost residual type and trap preservation type. The trap preservation type is more conducive to the preservation of shale gas, which is a the most favorable structural mode for shale gas exploration.